On Prime Near-Rings with Generalized Derivation - Howard E. Bell (International Journal of Mathematics and Mathematical Sciences)
Let N be a 3-prime 2-torsion-free zero-symmetric left near-ring with multiplicative center Z. We prove that if N admits a nonzero generalized derivation f such that f(N)⊆Z, then N is a commutative ring. We also discuss some related properties.